The drug-induced phenotypic landscape of colorectal cancer organoids - Betge, Johannes; Rindtorff, Niklas; Sauer, Jan; Rauscher, Benedikt; Dingert, Clara; Gaitantzi, Haristi; Herweck, Frank; Srour-Mhanna, Kauthar; Miersch, Thilo; Valentini, Erica; Boonekamp, Kim E.; Hauber, Veronika; et al. (Nature Communications, 2022)
Patient-derived organoids resemble the biology of tissues and tumors, enabling ex vivo modeling of human diseases. They have heterogeneous morphologies with unclear biological causes and relationship to treatment response. Here, we use high-throughput, image-based profiling to quantify phenotypes of over 5 million individual colorectal cancer organoids after treatment with >500 small molecules. Integration of data using multi-omics modeling identifies axes of morphological variation across organoids: Organoid size is linked to IGF1 receptor signaling, and cystic vs. solid organoid architecture is associated with LGR5 + stemness. Treatment-induced organoid morphology reflects organoid viability, drug mechanism of action, and is biologically interpretable. Inhibition of MEK leads to cystic reorganization of organoids and increases expression of LGR5, while inhibition of mTOR induces IGF1 receptor signaling. In conclusion, we identify shared axes of variation for colorectal cancer organoid morphology, their underlying biological mechanisms, and pharmacological interventions with the ability to move organoids along them.